Challenging Behavior and Related Factors in People with Intellectual Disability Living in Residential Care Centers in Israel - Sinai, Amanda; Tenenbaum, Ariel; Aspler, Shoshana; Lotan, Meir; Morad, Mohammed; Merrick, Joav (Frontiers in Public Health, 2013)
Introduction: People with intellectual disabilities have higher rates of mental ill-health and problem behaviors than the general population. Method: In this study, we present data on trends in challenging behavior in residential care centers in Israel from 1998-2008 and further data on trends in employment of psychiatrists from 1998-2009 and psychotropic medication use from 1998–2008. Data was collected from annual questionnaires sent out to all residential care centres in Israel, from the Office of the Medical Director, Division for Intellectual and Developmental Disabilities, Ministry of Social Affairs and Social Services. Results: Rates of challenging behaviors in people with intellectual disabilities living in residential care centres in Israel continues to rise. Alongside this, trends in regular psychotropic medication use also continues to increase. Conclusion: Consideration of biological, psychological, social and environmental factors in the assessment and management of people with challenging behaviors is important. This is best conducted using a multidisciplinary approach. This may include psychiatric assessment and consideration of medication, although non-pharmacological interventions should always be considered either alongside, or instead of medication.